Faktor-Faktor yang Memengaruhi Pertumbuhan Laba pada Koperasi Berkah Daha di Kabupaten Hulu Sungai Selatan: Pendekatan ARDL - Muhammad Alfiano Rizky; Luthfi Fatah; Nuri Dewi Yanti (Universitas Galuh, 2026)
Palm oil plantation cooperatives operating under the plasma-nucleus scheme on wetland areas in South Kalimantan face a condition where asset growth is not accompanied by improved profitability. This study aims to: (1) analyze profitability and solvency indicators of Koperasi Berkah Daha for the 2018–2024 period, (2) examine the effects of Fresh Fruit Bunch (FFB) price, FFB harvest volume, and regional inflation on profit growth using the Autoregressive Distributed Lag (ARDL) model. Monthly data from January 2018 to December 2024 (84 observations) were analyzed. Results indicate a consistent profitability decline: Net Profit Margin (NPM) fell from 21.49% (2021) to 14.16% (2024), Return on Assets (ROA) from 6.11% to 3.20%, and Return on Investment (ROI) from 7.03% to 3.89%, while the Debt to Equity Ratio (DER) averaged 0.20. The ARDL(8,9,7,6) model confirms cointegration (F-statistic = 8.357 > upper bound 3.862). In the long run, FFB price has a significant negative effect (coefficient −0.471, p = 0.008), harvest volume is insignificant, and regional inflation has a significant positive effect (coefficient 533.677, p = 0.001). The Error Correction Term (ECT) of −8.154 indicates overcorrection and high profit growth volatility.